Analisis Efektivitas TikTok pada Produk Ms Glow dalam Meningkatkan Kesadaran Merek: Brand Awareness - Nurazizah, Eka Mei; Redyansyah, Dino Taufiq; Rizqiyah, Nur Zahrotur; Almagrobi, Alaika Asrori; Amalia, Agustina Rizky (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effectiveness of TikTok in increasing brand awareness of MS Glow products at Mirza Beauty Store, Pasuruan. The method used is descriptive qualitative with data collection techniques of observation, interview, and content analysis. The results showed that Mirza Beauty Store has managed to significantly increase its sales through the TikTok platform. The strategies used include creative and educational content, live streaming, and TikTok Ads. These contents attracted the attention of potential customers and provided useful information, thus increasing awareness of the MS Glow brand. Suggestions for Mirza Beauty Store are to continue developing relevant and interesting content, collaborating with influencers, utilizing TikTok advertising features, and conducting careful data analysis.